Novel Approach Toward Plasma Enhancement in Trench-Insulated Gate Bipolar Transistors - Antoniou, M.; Lophitis, Neophytos; Bauer, F.; Nistor, I.; Bellini, M.; Rahimo, M.; Amaratunga, G.; Udrea, F. (My University, 2015)
In this letter, a trench-insulated gate bipolar transistor (IGBT) design with local charge compensating layers featured at the cathode of the device is presented and analyzed. The superjunction or reduced surface effect proves to be very effective in overcoming the inherited ON-state versus breakdown tradeoff appearing in conventional devices, such as the soft punch through plus or field stop plus (FS+) IGBTs. This design enhances the ON-state performance of the FS+IGBT by increasing the plasma concentration at the cathode side without affecting either the switching performance or the breakdown rating.
Keywords: Insulated Gate Bipolar Transistor (IGBT); superjunction power MOSFET; technology trade-off